Empowerment and turnover of nurse managers before and after a major health care reform in Cyprus: A cross sectional study - Leontiou, Ioannis; Papastavrou, Evridiki; Middleton, Nicos; Merkouris, Anastasios (My University, 2022)
Aim:This study aimed to investigate the perceived empowerment and turnoverintention of middle nurse managers before and after the implementation of a majorreform of the health care system in Cyprus, which also includes the transition of pub-lic hospitals towards administrative and financial autonomy.Background:The empowerment of nurse managers is important since previous stud-ies have shown that it is associated with performance at work and may have animpact on their turnover intention.Methods:A repeated cross-sectional study was conducted in March 2019 (firstphase) and was repeated in March 2020 (second phase), after the introduction ofmajor changes. The target population was all nurse managers of the public hospitals.The final sample consisted of 175 (RR 94%) participants in the first phase and178 (RR 95.6%) in the second.Results:Measurements at both time points revealed moderate levels of perceivedempowerment among Cyprus nurse managers. Empowerment score (17.95)appeared slightly lower at the repeat measurement compared to the first empower-ment score (18), but the observed difference was not statistically significant(p=0.184). Among the categories of empowermentopportunitieswas presentingstatistically significant differences between the two phases. At the second phase,mean scores of empowerment were consistently lower among those who statedYEScompared to those who statedNOin relation to (a) the intention to change depart-ment, (b) the intention to change profession and (c) the intention to change organiza-tion/hospital.Conclusions:This study demonstrated lower levels of empowerment among nursemanagers with turnover intentions. It is therefore needed to be investigated furtherReceived: 30 November 2021 Revised: 25 January 2022 Accepted: 23 March 2022DOI: 10.1111/jonm.136061196© 2022 John Wiley & Sons LtdJ Nurs Manag.2022;30:1196–1205.wileyonlinelibrary.com/journal/jonmwhether lower empowerment levels are the main reason for turnover intentions. Italso suggests the need for senior management to create opportunities and todevelop and implement interventions which aim to maintain and further improve theempowerment of the nurse managers and assess their effectiveness in terms of turn-over intention in the organization.Implications for nursing policy:The senior management of the hospitals needs toadopt retention strategies by establishing an empowered positive working environ-ment for nurse managers. Nurse managers need to collaborate with the senior man-agement and seek more access to opportunities, information, support and resourceswhich will enable them to perform their duties with efficiency and be more effective.
Keywords: Empowerment; Nurse managers; Turnover intention